Efficiency and Legitimacy : Trade-Offs in IMF Governance - Cottarelli, Carlo (IMF Working Papers; Working Paper ;, 2005)
Designing appropriate governance structures for an international financial institution such as the IMF is difficult, because steps to enhance the legitimacy of such an institution through constraints on its decision-making process may affect its operational efficiency. Potential trade-offs between legitimacy and efficiency exist for any public institution but are arguably more severe for an international one, because delegating power to it politically controversial and, thus, likely to imply tighter constraints. The paper also underscores that the trade-offs are not absolute, however: they depend on the specific ways in which legitimacy is pursued-that is, on the specific constraints that are set. Strategic reforms should, thus, aim at improving the terms of the trade-off by exploring steps that are Pareto-improving in the dimensions of legitimacy and efficiency.